THE IDEAL FRAMEWORK OF A QUR’AN-BASED IN STRENGTHENING SOCIO-ECONOMIC RIGHTS OF WOMEN IN PREVENTION FROM DOMESTIC VIOLENCE CASES IN MALAYSIA - Nadzrah Ahmad,; Rahmawati Mohd Yusoff,; Mohammad Hidir Baharudin, (Journal of Islamic, Social, Economics and Development, 2023)
Gender inequality in terms of economic participation and social standing of women appears to have contributed to violations of women's rights. As a result, women's economic empowerment is critical in ensuring equal social treatment. Inequality in gender treatment can lead to abuse, harassment, and violence. Should the people be concerned about women's rights, which are already enshrined in the Qur'an, these breaches and violations are unacceptable. Hence, this research aims to examine the governing Qur’anic principles on women’s socio-economic rights and to propose the ideal Qur’an-based framework in strengthening socio-economic rights of women in prevention from domestic violence cases in Malaysia. The analysis is based on a qualitative which involves a textual inductive method of research, and employs content and non-doctrinal analysis. The research suggest that the government improve the effectiveness of the available mechanisms and frameworks by adapting the principles outlined in Qur’an and Sunnah to strengthen women's empowerment in the economic sector in Malaysia.